2023
DOI: 10.1111/myc.13598
|View full text |Cite
|
Sign up to set email alerts
|

Application of deep learning algorithm in the recognition of cryptococcosis and talaromycosis skin lesions

Abstract: Fungal pathogens and infections are a growing global public health concern, with those most at risk being those with underlying health conditions or weakened immune systems. In recent years, the incidence and mortality of invasive fungal infections such as cryptococcus and talaromycosis have increased with the increase in HIV infection, the use of malignant tumours, organ transplantation and immunosuppressive age. 1,2 Cryptococcosis, an invasive fungus caused by Cryptococcus, is the third most common invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“… 3 However, the presentation can vary in non-HIV patients with different morphologies. 11 According to a study by He et al, nodules and subcutaneous abscesses comprise a higher proportion of skin lesions in non-HIV patients. 9 Another study by Chan et al reported that umbilicated lesions rarely occur in non-HIV patients.…”
Section: Discussionmentioning
confidence: 99%
“… 3 However, the presentation can vary in non-HIV patients with different morphologies. 11 According to a study by He et al, nodules and subcutaneous abscesses comprise a higher proportion of skin lesions in non-HIV patients. 9 Another study by Chan et al reported that umbilicated lesions rarely occur in non-HIV patients.…”
Section: Discussionmentioning
confidence: 99%